Two-dimensional magnetism in the pnictide superconductor parent material SrFeAsF probed by muon-spin relaxation - Baker, P; Franke, I; Lancaster, T; Blundell, S; Kerslake, L; Clarke, S (2009)
We report muon-spin relaxation measurements on SrFeAsF, which is the parent compound of an iron-arsenic- fluoride based series of superconducting materials. We find that this material has very similar magnetic properties to LaFeAsO, such as separated magnetic and structural transitions (TN =122 K, Ts =175 K), contrasting with SrFe2 As2 where they are coincident. The muon oscillation frequencies fall away very sharply at TN [β=0.22 (3)], which suggests that the magnetic exchange between the layers is weaker than in comparable oxypnictide compounds. Our specific-heat measurements show that a small but distinct feature occurs at Ts. There is no anomaly evident at TN as is typical for quasi-two-dimensional magnets. The magnetic entropy change between 100 and 185 K is ΔS=0.5 J mol-1 K-1. © 2009 The American Physical Society.